YOGYAKARTA SPECIAL PROVINCIAL GOVERNMENT POLICY IN EFFORTS TO INCREASE ORIGINAL LOCAL GOVERNMENT REVENUE AFTER THE COVID-19 PANDEMIC - Prayitno, Immanuella Christin; Diamantina, Amalia; Wibawa, Kadek Cahya Susila (CREPIDO, 2023)
The Covid-19 pandemic has also impacted the Yogyakarta Special Region (DIY) sector. In 2020, the DIY city government anticipated a reduction of original DIY local government revenue from the previous target of 50%. The purpose of this research is to know the urgency of the policy of the provincial government of DIY in terms of the PAD after the pandemic of Covid-19 and to analyse the policy of the local government of DIY in terms of PAD expansion after the Covid-19 pandemic. The researcher used normative legal research for the study. The researcher used three methods of problem-based approach the statutory approach, the historical approach and the conceptual approach, which have the descriptive and prescriptive methods of specification research. In conclusion, the DIY provincial government policy's urgency in increasing the PAD after the Covid-19 pandemic is that the PAD experienced a contraction of 6,87% in 2021.